Exploring students' beliefs about learning English in two public institutions (2011)
This article aims at raising awareness about student´s beliefs about English learning in two public institutions at the high school and university levels. The main objectives are, first, to establish the similarities and differences among these groups of students exploring their ideas and thoughts about what learning a foreign language, like English means in their lives, and second, to find some relations between the students’ experiences and their beliefs about English learning. It is worth mentioning that this issue has not been explored in our Colombian educative context, there are some studies about beliefs focusing their interest on teachers, but this small scale project explores this issue with students.